OCCUPATIONAL RISK ASSESSMENTS OF HEMATOLOGICAL PARAMETERS ALTERATIONS OF KAR OIL REFINERY WORKERS IN ERBIL PROVINCE, KURDISTAN REGION, IRAQ - ABDULKAREEM, ARAM QASIM; MOHAMMED , BUSHRA MOHAMMED AMIN (Journal of Duhok University, 2023)
Workers at petroleum refineries are exposed to an extensive variety of toxic chemical compounds utilized in the production of petroleum derivatives. A total of 100 participants were participated in this study, which consisted of two groups, the first group constitute 60 refineries workers (34 non-smokers and 26 smokers), the second group constitute of 40 control participants (20 non-smokers and 20 smokers). The main objective of this work was to demonstrate the possible effects of the mixture of hydrocarbon compound gases and vapors emitted from petroleum products on different hematological parameters (complete blood picture), as well as to reveal the correlation of those biomarkers with exposure period, smoking habit, age, and body mass index of workers at Kar refinery. Data showed significant reduction in hemoglubin, hematocrite, mean corpuscular hemoglubin, mean corpuscular hemoglubin concentration and elevation in red cell distribution width value in the exposed workers when compared to controls. A negative correlation was revealed between platelets and body mass index, and between hemoglubin and service period within the refinery. This study concluded that the observed changes in blood parameters may refer to damage in the hematopoietic system due to continuous exposure to vapors of petroleum product